Analisis Bibliometrik tentang Kematangan Digital dan Dampaknya terhadap Keamanan Siber - Kartika Putri, Aulia; Nurmandi, Achmad; Lawelai, Herman; Younus, Muhammad (The Journal of Society and Media, 2025)
Rapid digital transformation has prompted organisations to improve digital maturity in response to increasingly complex cybersecurity challenges. This research aims to explore the relationship between digital maturity and the effectiveness of data security measures, with a bibliometric approach to analyze trends, patterns and gaps in related literature. Based on the literature review, digital maturity reflects the level of digital technology adoption integrated with organisational strategy and culture, which is shown to have a significant impact on strengthening data security measures. This study used a bibliometric analysis method based on data from Scopus, involving 315 documents analyzed with VOSviewer and RStudio software to visualize trends and relationships between key variables. The results show that organizations with high digital maturity tend to be more capable of implementing effective data security measures, such as encryption, multi-factor authentication, and cybersecurity frameworks. In addition, the adoption of technologies such as blockchain and artificial intelligence (AI) also contributes to increased resilience against cyber threats. However, the gap between theory and real applications remains a challenge, with the need for more applicable and contextualized models. This research provides important insights for policymakers and practitioners to support a secure and sustainable digital transformation.